Investigation on the Incidence of Nonsuicidal Self-Injury Among Adolescents in China - Long, LiuYan (Pacific International Journal, 2024)
This study investigates the incidence and influencing factors of nonsuicidal self-injury (NSSI) among adolescents in China. Using a group sampling method, 1,368 students from a high school in Guangxi Province participated in the study by completing electronic questionnaires. The NSSI diagnostic criteria from the DSM-5 were applied to identify cases. Results revealed an NSSI incidence rate of 18.72%, with no significant gender differences. However, significant variations were observed based on age, residence, mental health status, family environment, social relationships, and academic performance. The study underscores the need for targeted prevention and intervention programs by health sectors, educational institutions, and policymakers to mitigate the prevalence of NSSI and promote adolescent mental health.